2021
DOI: 10.15295/bmij.v9i4.1919
|View full text |Cite
|
Sign up to set email alerts
|

Perakendecilikte drone ile ürün teslimatının tüketicilerin davranışsal niyetlerine etkisi

Abstract: Bu çalışmanın amacı, perakendecilikte drone ile ürün teslimatının tüketicilerin davranışsal niyetleri üzerindeki etkisini incelemektir. Online anket ve deney yöntemi kullanılarak katılımcılardan toplanan 404 veri için istatistiksel analizler yapılmıştır. Tek örneklem t-testi sonuçlarına göre; drone ile ürün teslimatı, tüketicilerin drone'ları alışveriş için kullanma davranışsal niyetleri üzerinde olumlu ve anlamlı bir etkiye sahiptir. Bağımsız örneklemler t-testi sonuçlarına göre; erkek ve kadınlar arasında ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The results showed that perceived privacy risk did not significantly affect attitude. Some researchers argue that perceived risk significantly negatively affects attitudes (Meidute-Kavaliauskiene et al, 2021), while others claim that it does not significantly affect attitudes (Çelik & Aydın, 2021). The sample consisted of participants who have experienced IoT services and have a high level of education.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that perceived privacy risk did not significantly affect attitude. Some researchers argue that perceived risk significantly negatively affects attitudes (Meidute-Kavaliauskiene et al, 2021), while others claim that it does not significantly affect attitudes (Çelik & Aydın, 2021). The sample consisted of participants who have experienced IoT services and have a high level of education.…”
Section: Discussionmentioning
confidence: 99%
“…The study's findings demonstrate that drone technology will play a significant role in the logistics industry in the future. Çelik and Aydın (2021) have made a convincing case for why consumers might employ drone delivery services for retail goods. Turğut and Şeker (2022 were reviewed the usage of drone transportation in logistics organizations, as well as their applications.…”
Section: Business Andmentioning
confidence: 99%
“…Aydin (2022),Chen et al (2022),Choe et al (2021a),Choe et al (2021b),Çelik and Aydın (2021),Frazier (2021),Ganjipour and Edrisi (2022),Hwang and Choe (2019),Hwang and Kim (2019),Hwang and Kim (2020), Hwang et al (2019a), Hwang et al (2019b), Hwang et al (2020a), Hwang et al (2020b), Hwang et al (2021a), Jasim et al (2022), Khan et al (2019), Kim and Hwang (2020), Kim et al (2021), Leon et al (2021), Liu et al (2020), Mathew et al (2021), Michels et al (2021), Mittendorf et al (2017), Napaporn (2020), Osakwe et al (2022), Sham et al (2022), Waris et al (2022), Yaprak et al (2021) and Yoo et al (2018) are the thirty studies selected for this current study. Accordingly, there are empirical studies conducted on drone delivery from 2017 to the present (i.e.…”
mentioning
confidence: 99%